Revealing fine-scale spatiotemporal differences in SARS-CoV-2 introduction and spread - Gage K. Moreno (Nature Portfolio, 2020)
In this study, the authors present an analysis of 247 full-genome SARS-CoV-2 sequences obtained from two communities in Wisconsin, USA, and report distinct patterns of viral spread. Their results suggest that patterns of SARS-CoV-2 transmission and spread may vary substantially, even between neighbouring communities.